Modeling the demand for the suburban passenger operations - Горбачов, Петро Федорович; Крикун, Вадим Іванович; Акбар, Джан Полад (Eastern-European Journal of Enterprise Technologies, 2013)
The approaches available for the modeling of the demand for suburban passenger operations cannot be used by different reasons. Therefore, special technique should be developed. The objective of this effort is to develop an algorithm for the determination of demand for the local route transportation on the basis of the known capacities of departure and arrival stops. The problems related to the determination of departure and arrival capacities can be solved using the tabular procedure of survey at the stops. The proposed technique allows for the search of a certain set, which would describe the range boundaries for the possible values of a matrix and not a single version of it. This algorithm used for the computation of suburban passenger correspondences allows us to obtain some versions of initial data that can be used for the modeling of the conveyance process of passengers and these versions will simultaneously serve as possible options for the description of the demand for public conveyance